PHP, MySQL, & JavaScript : all-in-one for dummies - Blum, Richard (Hoboken, New Jersey : Wiley, 2018)
Learn the languages that run the web. PHP, MYSQL, and JavaScript are the key technologies behind your favorite websites. When you understand them, you're well on your way to building cool websites and possibly a lucrative new career. Whether you're brand-new to programming or you want to brush up on specific areas, these seven minibooks will take you step-by-step through the essentials of building your own web development environment, as well as coding the front and back ends of professional websites.--
Introduction -- Book 1: Getting started with web programming. Examining the pieces of web programming ; Using a web server ; Building a development environment -- Book 2: HTML5 and CSS3. The basics of HTML5 ; The basics of CSS3 ; HTML5 forms ; Advanced CSS3 ; HTML5 and multimedia -- Book 3: JavaScript. Introducing JavaScript ; Advanced JavaScript coding ; Using jQuery ; Reacting to events with JavaScript and jQuery ; Troubleshooting JavaScript programs -- Book 4: PHP. Under PHP basics ; PHP flow control ; PHP libraries ; Considering PHP security ; Object-oriented PHP programming ; Sessions and carts -- Book 5: MySQL. Introducing MySQL ; Administering MySQL ; Designing and building a database ; Using the database ; Communicating with the database from MySQL scripts -- Book 6: Creating object-oriented programs. Designing an object-oriented application ; Implementing an object-oriented application ; Using AJAX ; Extending WordPress -- Book 7: Using PHP frameworks. The MVC method ; Selecting a framework ; Creating an application using frameworks.
Includes index.
Keywords: MySQL (Electronic resource); MySQL (Electronic resource); PHP (Computer program language); JavaScript (Computer program language); Web site development; JavaScript (Computer program language); PHP (Computer program language); Web site development; Nonfiction